Synapsin I deficiency results in the structural change in the presynaptic terminals in the murine nervous system (The Rockefeller University Press, 1995)
Synapsin I is one of the major synaptic vesicle-associated proteins. Previous experiments implicated its crucial role in synaptogenesis and transmitter release. To better define the role of synapsin I in vivo, we used gene targeting to disrupt the murine synapsin I gene. Mutant mice lacking synapsin I appeared to develop normally and did not have gross anatomical abnormalities. However, when we examined the presynaptic structure of the hippocampal CA3 field in detail, we found that the sizes of mossy fiber giant terminals were significantly smaller, the number of synaptic vesicles became reduced, and the presynaptic structures altered, although the mossy fiber long-term potentiation remained intact. These results suggest significant contribution of synapsin I to the formation and maintenance of the presynaptic structure.